2017
DOI: 10.1002/jcp.26254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of XIST/miR‐137 axis on neuropathic pain by targeting TNFAIP1 in a rat model

Abstract: Non-coding RNAs have been reported to participate in the pathophysiology of neuropathic pain. The objective of our study was to investigate the biological role of XIST in neuropathic pain development. In our study, we identify and validate that lncRNA XIST was markedly increased and miR-137 was significantly decreased in chronic constriction injury (CCI) rats. XIST silencing alleviated pain behaviors including both mechanical and thermal hyperalgesia in the CCI rats. XIST was predicted to interact with miR-137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…A recent report showed upregulation of Xist in spinal cord from rat chronic constriction injury model of neuropathic pain, and silencing Xist alleviated both mechanical and thermal hyperalgesia. 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report showed upregulation of Xist in spinal cord from rat chronic constriction injury model of neuropathic pain, and silencing Xist alleviated both mechanical and thermal hyperalgesia. 41 …”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are fine tuners of gene regulation and can induce nuanced knockdown of its target mRNAs. Downregulation of Xist by siRNAs was recently shown to decrease pain hypersensitivity 41 in mouse model of neuropathic pain. miR-34a is a tumor suppressor and currently in Phase 1 clinical trials for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently found that the expression of XIST was promoted by activated NF-κB pathway and, in turn, XIST generated a negative feedback loop to regulate NF-κB/NLRP3 inflammasome pathway for mediating the process of inflammation [38]. Zhao et al also reported that targeting XIST inhibited NF-kB activity, which serving as a therapeutic target in neuropathic pain [39]. In our study, we found that targeting XIST results in constitutive activation of NF-κB and p65 nucleus translocation and PUMA signal pathway, whereas P65 inhibition could attenuate the PUMA signal expression in the XIST shRNA transfected U2OS cells, demonstrating that XIST could modulate PUMA signaling through activation of P65.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to examine miRNA-13 rs1625579 polymorphisms in patients with KD. Recent research showed that overexpression of miRNA-13 significantly inhibited tumor necrosis factor alpha-induced protein 1 (TNFAIP1) production both in vivo and in vitro, 30 and miRNA-13 suppressed vascular smooth muscle cell proliferation and migration. 31 Overexpression of miR-137 inhibited upregulation of the inflammatory cytokines IL-6, VCAM-1 and ICAM-1, and human umbilical vein endothelial cell angiogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%